Bitter Melon: A Comprehensive Review: Review: Bitter Melon Review - Makkia Saleem; Mian Kamran Sharif; Roma Saleem (Biological Sciences - PJSIR, 2022)
Medicinal plants are used widely to prevent, cure and treat health related complications and become popular as an alternative therapy. A wide variety of medicinal plants and their different products have been used in various cultures because of their bioactive components. Since ancient times, medicinal plants with numerous bioactive components have been used traditionally, not only by laymen but also by physicians to treat a variety of human health disorders such as cancer, coronary heart diseases, and diabetes. Momordica charantia Linn. (bitter melon) is an example of such a vegetable plant frequently used for medicated purposes. It is a common and traditional food in Asian cuisine. It is known for controlling the blood glucose level in the body and used as a remedy by the practitioner of complementary and alternative medicines (CAM). Bitter melon has bioactive components such as alkaloids, vicine, steroids, charantin and certain protein types (P-insulin, V-insulin) that are responsible for the hypoglycemic response.